Effectiveness Of Road Maintenance Competency Training Model For Fresh Graduates Of Civil Engineering - Kadir, Yuliyanti; Hamsu Abdul Gani; Darmawang, Darmawang (International Journal of Education, Vocational and Social Science, 2024)
For fresh graduates it is not easy to get a job, because the number of undergraduate graduates is increasing every year, but the available job vacancies are not proportional to the number of graduates currently available. One of the processes of developing and improving the competence of fresh graduates can be done by carrying out training activities. Through participation in training, fresh graduates are able to improve their competence in construction work, especially road maintenance. The type of research used is quantitative research with One Group pre test - post test design. In this model there is one class given treatment and then the process and results are observed. The research instrument used was a road maintenance learning outcomes test instrument for fresh graduates of the Civil Engineering study programme. The test was conducted at the beginning of the meeting (pre test) and the end of the meeting (post test). The research analysis used N-Gain score. Based on the pre-test and post-test scores of the road maintenance training, there was a significant increase in the average score of the participants. During the pre-test, the minimum score obtained by participants was 42 and the maximum was 75, with an average score of 60 and a standard deviation of 9.72. The post test results showed a positive increase in participants' achievements. The minimum score on the post test was 83 and the maximum score was 100, with an average score of 89 and a standard deviation of 4.7. This indicates that the training was successful in significantly improving participants' competencies, with a difference between the mean pre and post test scores of 29 points. The average N-gain for all participants was 0.7, which falls into the high improvement category. This shows that the training was effective in improving the overall competence of the participants, with a visible impact on the improvement of their scores after the training.